Influence of periodontal inflammation on tryptophan-kynurenine metabolism: A cross-sectional study - Kurgan, Şivge; Önder, Canan; Balcı, Nur; Akdoğan, Nihan; Altıngöz, Sema Merve; Serdar, Muhittin Abdulkadir; Günhan, Meral (Springer Heidelberg, 2022)
Objectives Kynurenine pathway (KP) is the primary way of degrading tryptophan (TRP) and generates several bioactive metabolites (such as kynurenine (KYN), kynurenic acid (KYNA), 3-hydroxykynurenine (3OHKYN)) to regulate biological processes that include host-microbiome signaling and immune cell response. This study is aimed to determine the relationship between periodontal inflammation and tryptophan-kynurenine metabolism and identify their association with periodontal clinical parameters. Materials and methods Saliva and serum samples were collected from 20 stage III, grade B generalized periodontitis patients, and 20 periodontally healthy control individuals. Samples were analyzed for IL-6, KYN, TRP, KYN/TRP ratio, KYNA, 3OHKYN, picolinic acid (PA), and quinolinic acid (QA) by liquid chromatography-mass spectrometry. Clinical periodontal parameters (plaque index (PI), probing pocket depth (PPD), gingival recession (GR), clinical attachment loss (CAL), and bleeding on probing (BOP)) were recorded. Results Clinical parameters were significantly higher in the periodontitis group (p < 0.001). Salivary IL-6, TRP, KYN, KYNA, PA, and QA levels were significantly higher and KYN/TRP ratio was significantly lower in periodontitis group than control group (p < 0.05). Serum KYN, KYN/TRP ratio and PA levels were significantly higher in periodontitis group than control group (p < 0.05). PPD, BOP, PI, and CAL had significantly positive correlations with salivary IL-6, TRP, PA, QA, and serum KYN and significantly negative correlations with salivary KYN/TRP ratio. Conclusions Our results suggest that periodontal inflammation plays a role in local and systemic tryptophan-kynurenine metabolism.
Keywords: Kynurenine Pathway; Periodontitis; Tryptophan